Cardiovascular Metrics Associated With Prevention of Aging-Related Parkinsonian Signs Following Exercise Intervention in Sedentary Older Rats - Kasanga, Ella A.; Little, Joel; McInnis, Tamara R.; Bugnariu, Nicoleta; Cunningham, J. Thomas; Salvatore, Michael F. (Frontiers in Aging Neuroscience, 2021)
Preservation of motor capabilities is vital to maintaining independent daily living throughout a person's lifespan and may mitigate aging-related parkinsonism, a progressive and prevalent motor impairment. Physically active lifestyles can mitigate aging-related motor impairment. However, the metrics of physical activity necessary for mitigating parkinsonian signs are not established. Consistent moderate intensity (~10 m/min) treadmill exercise can reverse aging-related parkinsonian signs by 20 weeks in a 2-week on, 2-week off, regimen in previously sedentary advanced middle-aged rats. In this study, we initiated treadmill exercise in sedentary 18-month-old male rats to address two questions: (1) if a rest period not longer than 1-week off exercise, with 15 exercise sessions per month, could attenuate parkinsonian signs within 2 months after exercise initiation, and the associated impact on heart rate (HR) and mean arterial pressure (MAP) and (2) if continuation of this regimen, up to 20 weeks, will be associated with continual prevention of parkinsonian signs. The intensity and frequency of treadmill exercise attenuated aging-related parkinsonian signs by 8 weeks and were maintained till 23 months old. The exercise regimen increased HR by 25% above baseline and gradually reduced pre-intervention MAP. Together, these studies indicate that a practicable frequency and intensity of exercise reduces parkinsonian sign severity commensurate with a modest increase in HR after exercise. These cardiovascular changes provide a baseline of metrics, easily measured in humans, for predictive validity that practicable exercise intensity and schedule can be initiated in previously sedentary older adults to delay the onset of aging-related parkinsonian signs.